Existence and Uniqueness of Solutions for the Neutral Fractional Integro-Differential Equations with Fractional Integral Boundary Conditions - Hamoud, Ahmed A.; Sharif, Abdulrahman A.; Ghadle, Kirtiwant P. (Journal of Vibration Testing and System Dynamics, 2026)
In this paper, we establish sufficient conditions for the existence and uniqueness of solutions for a class of boundary value problems with integral condition for neutral fractional integro-differential equations. The results are established by the application of the contraction mapping principle, Leray-Schauder alternative theorem and Krasnoselskii fixed point theorem. An example is provided to illustrate the main results.